2016
DOI: 10.1080/01635581.2016.1187282
|View full text |Cite
|
Sign up to set email alerts
|

Fish Oil Supplementation Enhances Pulmonary Strength and Endurance in Women Undergoing Chemotherapy

Abstract: We investigated the effect of fish oil (FO) supplementation, at 4 g/day, on the respiratory performance and blood lipid profile of 32 patients with breast cancer at the beginning of chemotherapy. They were randomized into two groups: control (C) and FO supplemented (S). Both groups underwent three respiratory evaluations and blood harvest (before chemotherapy-Day 0, and 30 and 60 days after supplementation). The S group showed a significant increase in the maximal inspiratory and expiratory pressure (P ≤ 0.05 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Other studies have proven that the glucose metabolism of BC cells is probably influenced by nutrient and substrate availability and by nutrition. For example, plasma lactate concentrations were significantly lower after 60 days of fish oil supplementation in BC patients during adjuvant chemotherapy in respect to a control group [143]. Moreover, another study found that 12 weeks of a ketogenic, high-fat, and very low-carbohydrate diet were associated with a significant reduction in circulating lactate levels in comparison to a control group [144].…”
Section: Circulating Lactate In Breast Cancermentioning
confidence: 96%
“…Other studies have proven that the glucose metabolism of BC cells is probably influenced by nutrient and substrate availability and by nutrition. For example, plasma lactate concentrations were significantly lower after 60 days of fish oil supplementation in BC patients during adjuvant chemotherapy in respect to a control group [143]. Moreover, another study found that 12 weeks of a ketogenic, high-fat, and very low-carbohydrate diet were associated with a significant reduction in circulating lactate levels in comparison to a control group [144].…”
Section: Circulating Lactate In Breast Cancermentioning
confidence: 96%
“…The intervention group were 80% less likely to have nausea and vomiting, 92.8% less likely to have problems with bowel function, and 20% less likely to have poor appetite than the control group. In a study of fish oil supplementation, Suzumura et al (2016) reported significantly enhanced respiratory function (p<0.05), and significantly lower blood lactate concentration (p<0.05) in women in the intervention group compared to the control group who did not take the supplement.…”
Section: Approaches To Providing Nutritional Supportmentioning
confidence: 97%